PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI DI KANTOR KELURAHAN SUNGAI LILIN KABUPATEN MUSI BANYUASIN - Rully Alamsyah; Hendry Wijaya; Rendi Hidayat (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of emotional intelligence on employees at the Sungai Lilin Village Office, Musi Banyuasin Regency. This study used a quantitative method, this research was conducted on employees at the Sungai Lilin Village Office, the data sources for this research were primary data and secondary data using data collection techniques using questionnaires, interviews, observation and literature studies. The population in this study were employees at the Singai Lilin Village Office, the sample in this study was 59 respondents using Sugiyono's theory. The sampling technique uses non-probability sampling, namely accidental sampling (accidental sampling). The data processing technique of this study used the SPSS version 25. The results of this study showed that emotional intelligence (X) had an effect on employee performance (Y), this was obtained from a correlation value of 0.805 with a significance level of 1,000, which means emotional intelligence and employee performance has a high relationship, the coefficient of determination test (R2) is 0.647 meaning that the emotional intelligence variable affects employee performance by 64.7%, while the remaining 35.3% is influenced by variables not examined in this study. In the t-test (hypothesis test), the value of tcount > t-table is 6.175 > 2.002 and is corroborated by sig. t-test is 0.000 < 0.05, which means that emotional intelligence has an effect on improving employee performance.